ChemInform Abstract: Rhodium‐Catalyzed Tunable Oxidative Cyclization Toward the Selective Synthesis of α‐Pyrones and Furans. Issue 22 (12th May 2016) - Wu, Jiaping; Wang, Dongxu; Wan, Yanjun; Ma, Cheng
Abstract: Rh‐Catalyzed cyclization of N‐tosylacrylamides [e.g. (I)] and diazo compounds [e.g. (II)] gives fully substituted pyrones [e.g. (III)] in the absence of an external oxidant, while furans [e.g. (VIII)] are obtained in the presence of AgOAc as an external oxidant.